Propagation of Elastic Waves in Prestressed Media - Inder Singh; Dinesh Kumar Madan; Manish Gupta (Journal of Applied Mathematics)
3D solutions of the dynamical equations in the presence of external forces are derived for a homogeneous, prestressed medium. 2D plane waves solutions are obtained from general solutions and show that there exist two types of plane waves, namely, quasi-P waves and quasi-SV waves. Expressions for slowness surfaces and apparent velocities for these waves are derived analytically as well as numerically and represented graphically.